Hospital care in later life among former world-class Finnish athletes (Journal of the American Medical Association, 1996)
OBJECTIVE: To investigate the use of hospital care from all causes among former top-level athletes from different vigorous sports to determine whether health benefits or adverse effects have the greater influence. DESIGN: National, population-based cohort study with a 21-year follow-up. SETTING: Finland. SUBJECTS: A total of 2049 male athletes who had represented Finland during 1920 to 1965, and 1403 male controls classified healthy at 20 years of age. MAIN OUTCOME MEASURE: In-hospital care from all causes was extracted from the national hospital discharge registry for the period 1970 through 1990 expressed as hospital days per person-years of exposure. RESULTS: Compared with controls, the rate ratios (RRs) for all-cause hospital days per person-years of exposure were lower in athletes from endurance sports (RR, 0.71; 95% confidence interval [Cl], 0.70-0.73), mixed sports (including endurance and weight training) (RR, 0.86; 95% Cl, 0.85-0.87), and power sports (RR, 0.95; 95% Cl, 0.94-0.96) (P < .001 for all comparisons) after adjustment for age and occupational group. The lower RR among athletes from endurance sports and other sports involving aerobic activity was largely explained by lower rates of hospital care for heart disease, respiratory disease, and neoplasms, but not for musculoskeletal disorders. CONCLUSIONS: Former elite athletes, particularly those in aerobic sports, use less hospital care. Other beneficial health habits are known to be associated with a physically active lifestyle.